DEFIRENCED TREATMENT OF LUNG MALIGNANT TUMORS COMPLICATED WITH PLEURITIS (World Bulletin of Public Health, 2022)
This article provides information, treatment for malignant lung tumors and what drugs are used. The purpose of this study was to study the characteristics of the correlations between the above factors, the likelihood of the influence of the characteristics of the primary tumor on the intensity of accumulation, the clinical features of the course of hydrothorax
Keywords: chest; methods of nonspecific therapy; lung diseases; specific therapy of the pleural cavity and lungs